15 Bereavement during COVID-19: findings from a UK-wide online survey on the use and perceived helpfulness of informal and formal support during the pandemic. (30th January 2023) - Goss, Silvia; Mirra, Renata Medeiros; Longo, Mirella; Sivell, Stephanie; Seddon, Kathy; Torrens-Burton, Anna; Sutton, Eileen; Nelson, Annmarie; Byrne, Anthony; Selman, Lucy E; Harrop, Emily
Abstract : Introduction: Millions became bereaved during the pandemic, with many facing challenges accessing support. Aims: To describe the use and helpfulness of different types of support in a cohort of people bereaved during the pandemic in the UK. Methods: A longitudinal survey of people bereaved during the pandemic over four time points. At 7- and 13-months post-bereavement (T2 and T3), participants rated the helpfulness of support used and described how they had been helped by this support. Results: 420 participants completed at least one follow-up survey (T2, T3 or both). Most respondents were female (88.3%) and had lost a parent (57.6%) or partner (24.3%), with 3.3% from a minoritised ethnic background. Support from family and friends, reported by 89.3% of participants, was rated as 'quite helpful' (mean rating 4.3 out of 5), and included help with practical tasks, expressing feelings/sharing grief, remembering, feeling cared for and less isolated. The most commonly used form of other support was 1:1 support (e.g. counselling), used by 40.5% of participants, with an average helpfulness rating of 4.1, helping participants feel listened to and process their grief. Online community support, used by 31.0% of participants, was also rated 'quite helpful' (3.9), enabling sharing with similar others, feeling understood and less alone. Informal and formal bereavement groups were rated as similarly helpful (4.2) while helplines and specialist mental health support were slightly less helpful (3.6) (used by 9.3%, 4.8%, 7.1% and 4.5% of participants, respectively). Conclusions: Results demonstrate the perceived benefits and helpfulness of different forms of bereavement support used during the pandemic. Impact: These findings highlight the value of informal as well as formal support, particularly bereavement counselling. Policy makers must attend to the foundational and second tiers of the public health model of bereavement support, supporting communities as well as services.